Pengaruh Kesadaran Wajib Pajak, Sanksi Perpajakan Dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak (Studi Pada Wajib Pajak Kendaraan Bermotor di Kota Langsa) - Irfana, Muhardila; Rizal, Yani; Meutia, Tuti (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
This study aims to determine the effect of Taxpayer Awareness, Tax Sanctions and Fiscus Services on Taxpayer Compliance in Langsa City. The number of samples used in this study were 100 respondents who were calculated based on the Slovin formula with the method of determining the sample was random sampling. The data obtained were analyzed using the SPSS (Statistical Package For Social Sciences) analysis technique. The equation model analyzed is multiple linear regression analysis, classical assumption test and hypothesis testing (t test, F test and Determination Coefficient (R2)). The results of this study indicate that (1) Taxpayer awareness has a significant effect on Taxpayer Compliance, (2) Tax Sanctions have no significant effect on Taxpayer Compliance, (3) Fiscus Services do not have a significant effect on Taxpayer Compliance, (4) Taxpayer Awareness, Tax Sanctions and Fiscus Services simultaneously have a significant effect on Taxpayer Compliance.